2018
DOI: 10.1073/pnas.1712792115
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control over membrane-initiated steroid signaling with a DNA nanocapsule

Abstract: Membrane-initiated steroid signaling (MISS) is a recently discovered aspect of steroidal control over cell function that has proved highly challenging to study due to its rapidity and ultrasensitivity to the steroid trigger [Chow RWY, Handelsman DJ, Ng MKC (2010) Endocrinology 151:2411-2422]. Fundamental aspects underlying MISS, such as receptor binding, kinetics of ion-channel opening, and production of downstream effector molecules remain obscure because a pristine molecular technology that could trigger the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Using a well-characterized, icosahedral DNA nanocapsule reporter system (SI Fig. 3 & 4) 28,29 , we found that uncatalyzed thioldisulfide exchange mediated by small biologically available thiols was negligible.…”
Section: Tdx Detects Disulfide Exchange In Late Endosome In Vivomentioning
confidence: 97%
“…Using a well-characterized, icosahedral DNA nanocapsule reporter system (SI Fig. 3 & 4) 28,29 , we found that uncatalyzed thioldisulfide exchange mediated by small biologically available thiols was negligible.…”
Section: Tdx Detects Disulfide Exchange In Late Endosome In Vivomentioning
confidence: 97%
“…Immunostaining was done as described previously 58 . Briefly, Human monocyte derived macrophages (HMDMs) were differentiated on a glass bottom 3.5 cm imaging dish and treated with or without 100 ng/mL LPS for 24 hours.…”
Section: Immunostaining Of Myeloperoxidase (Mpo)mentioning
confidence: 99%
“…Other than the simple i-motif structure, a DNA icosahedra was also designed and used for cargo-loading, which was further employed in cell imaging. For example, they introduced three different endocytic ligand (folic acid (FA), galectin-3 (Gal3), and the Shiga toxin B-subunit (STxB)) to the quantum dot (QD)-loaded DNA icosahedra respectively through site-specific modification and demonstrated the feasibility to characterize the dynamics of endocytic pathways facilitated by Gal3 and STxB . Hence, the QD-loaded DNA icosahedra exhibited an excellent platform in real-time endocytic pathway mapping at single-particle level.…”
Section: Robots For Nanomedicinementioning
confidence: 99%